2022
DOI: 10.1101/2022.03.31.486607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A ROS-dependent mechanism to drive progression through S phase

Abstract: Long considered as cytotoxic reagents, reactive oxygen species (ROS) at the right concentration promote cell proliferation in cell culture, stem cells and model organisms. However, how ROS signaling is coordinated with cell cycle progression and integrated into the cell cycle control machinery on the molecular level remains unsolved. Here, we report oscillations of mitochondrial ROS during the cell cycle that target cyclin-dependent kinase 2 (CDK2). Chemical and metabolic interference with ROS production decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
1
1
0
Order By: Relevance
“…The results show that 62 key targets were mainly gathered in melanoma cells. By intersecting the key cluster and the intersection of drug-related genes and melanoma-related genes, we finally identified three crucial targets, EGFR, ERBB2, and CDK2, which are all protein serine/threonine kinases and are involved in cell cycle regulation (Lo and Hung, 2006;Hirai et al, 2017;Kirova et al, 2022). It has been reported that cinobufagin can inhibit the EGFR-CDK2 signaling pathway in hepatocellular carcinoma, which is consistent with our predicted results (Yang et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…The results show that 62 key targets were mainly gathered in melanoma cells. By intersecting the key cluster and the intersection of drug-related genes and melanoma-related genes, we finally identified three crucial targets, EGFR, ERBB2, and CDK2, which are all protein serine/threonine kinases and are involved in cell cycle regulation (Lo and Hung, 2006;Hirai et al, 2017;Kirova et al, 2022). It has been reported that cinobufagin can inhibit the EGFR-CDK2 signaling pathway in hepatocellular carcinoma, which is consistent with our predicted results (Yang et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, cellular metabolism and its redox potential associated play a crucial role in cell cycle regulation. In mitotic cells, the progression of cell division is accompanied by an increase in ROS levels, especially in the mitochondria [ 204 ]. ROS influence cell cycle progression in a context-dependent manner via phosphorylation and ubiquitination of CDKs and cell cycle regulatory molecules [ 205 ].…”
Section: Impact Of Ros On Biological Events In Agingmentioning
confidence: 99%